Immigrant screening for latent tuberculosis infection: numbers needed to test and treat, a Norwegian population-based cohort study. Issue 1 (17th January 2019) - Winje, Brita Askeland; Grøneng, Gry Marysol; White, Richard Aubrey; Akre, Peter; Aavitsland, Preben; Heldal, Einar
Abstract : Objectives: To estimate the number needed to screen (NNS) and the number needed to treat (NNT) to prevent one tuberculosis (TB) case in the Norwegian immigrant latent tuberculosis infection (LTBI) screening programme and to explore the effect of delay of LTBI treatment initiation. Design: Population-based, prospective cohort study. Participants: Immigrants to Norway. Outcome: Incident TB. Methods: We obtained aggregated data on immigration to Norway in 2008–2011 and used data from the Norwegian Surveillance System for Infectious Diseases to assess the number of TB cases arising in this cohort within 5 years after arrival. We calculated the average NNS and NNT for immigrants from the top 10 source countries for TB in Norway and by estimated TB incidence rates in source countries. We explored the sensitivity of these estimates with regard to test performance, treatment efficacy and treatment adherence using an extreme value approach, and assessed the effects of emigration, time to TB diagnosis (to define incident TB) and intervention timing. Results: NNS and NNT were overall high, with substantial variation. NNT showed numerically stronger negative correlation with TB notification rate in Norway (−0.75 [95% CI −1.00 to −0.44]) than with the WHO incidence rate (IR) (−0.32 [95% CI −0.93 to 0.29]). NNT was affected substantially by emigration and the definition of incident TB. Estimates were lowest for Somali (NNS 99 [70–150], NNT 27 [19–41]) and highest for Thai immigrants (NNS 585 [413–887], NNT 111 [79–116]). Implementing LTBI treatment in immigrants sooner after arrival may improve the effectiveness of the programme. Conclusion: Using TB notifications in Norway, rather than IR in source countries, would improve targeting of immigrants for LTBI management. However, the overall high NNT is a concern and challenges the scale-up of preventive LTBI treatment for significant public health impact. Better data are urgently needed to monitor and evaluate NNS and NNT in countries implementing LTBI screening.